Coronary Revascularization in Chronic and End-Stage Renal Disease: A Systematic Review and Meta-analysis. (January 2016) - Kannan, Arun; Poongkunran, Chithra; Medina, Raul; Ramanujam, Vendhan; Poongkunran, Mugilan; Balamuthusamy, Saravanan
Abstract : Patients with chronic kidney disease (CKD) and end-stage renal disease (ESRD) on dialysis have an increased risk for cardiovascular mortality and morbidity secondary to occlusive coronary artery disease. Optimal revascularization strategy is unclear in this high-risk population. We have performed a meta-analysis to compare coronary artery bypass grafting (CABG) versus percutaneous coronary intervention (PCI) in patients with ESRD and CKD. We searched PubMed, Ovid, MEDLINE, CINAHL, and EMBASE (1980–2013) and found 17 trials (N = 33, 584) in the ESRD arm and 6 studies (n = 15, 493) in the CKD arm. Two investigators independently collected the data. All the studies were retrospective trials. In the ESRD and CKD groups, we found significantly reduced early mortality with the PCI group with the odds ratio of 2.08 (1.90–2.26; P < 0.00001) and 2.55 (1.45–4.51; P = 0.001), respectively. Contrary to the early mortality results, we found decreased late mortality with the CABG group when compared with the PCI group [odds ratio: 0.86 (0.83–0.89; P < 0.000001) and 0.82 (0.76–0.88; P < 0.00001)] in the ESRD and CKD arm, respectively. When compared with PCI, there was decreased cardiovascular mortality with an odds ratio of 0.61 (0.40–0.92; P = 0.02) in patients who underwent CABG in ESRD population. Similar trends were observed in the incidence of myocardial infarction and repeat revascularization. There is a strong trend for decreased risk of stroke with PCI when compared with CABG in ESRD and CKD populations.